Volume transition of PNIPAM in a nonionic surfactant hexagonal mesophase - Jijo, V. J.; Sharma, Kamendra P.; Mathew, Renny; Kamble, Samruddhi; Rajamohanan, P. R.; Ajithkumar, Thalasseril G.; Badiger, Manohar V.; Kumaraswamy, Guruswamy (Macromolecules, 2010)
We investigate the volume transition of a thermoresponsive polymer, poly(N-isopropylacrylamide), PNIPAM, in the presence of an aqueous solution of nonionic surfactant, C(12)E(9). We combine turbidimetry with optical microscopy, NMR, and SAXS to follow the volume transition of the PNIPAM and the H(1)-isotropic transition of the surfactant/water system. Nonionic surfactants such as C(12)E(9) are known to interact weakly with PNIPAM. Accordingly, we show that there is only a small change in the volume transition temperature for the PNIPAM in isotropic micellar solutions of C(12)E(9), even for relatively high concentrations of C(12)E(9). Interestingly, once the surfactant forms an H(1) phase, there is a dramatic decrease in the coil globule transition onset temperature. We believe that this behavior results from a competition between C(12)E(9) in the H(1) phase, and PNIPAM to associate with water. When PNIPAM in the H(1) phase is cooled to low enough temperatures so as to be in the coil state, it locally disturbs the hexagonal phase ordering. Thus, we show that for PNIPAM in a weakly interacting surfactant matrix, it is the phase behavior of the matrix rather than the matrix chemistry that governs the coil globule transition. Finally, we show that in a PNIPAM copolymer with a higher LCST we observe an interesting sequence of transitions in the surfactant phase: on cooling from a high temperature free-blowing turbid globular state (similar to 75 degrees C), we enter a free-flowing translucent coil phase (similar to 47 degrees C), then a turbid gel (similar to 25 degrees C) where the copolymer is collapsed in the HI phase, and finally a low-temperature clear gel (similar to 5 degrees C) where the copolymer is in the expanded coil state.

Viscoelastic liquid from regenerated silk fibroin in the silk i conformation: a writeable and shapeable material - Kumar, Raj; Joseph, Emmanuel; Chaudhari, Atul; Nisal, Anuya; Sharma, Kamendra P. (ACS Applied Polymer Materials, 2022)
Regenerated silk fibroin (RSF) has acquired enormous attention because of its exceptional toughness, strength, and biocompatible nature. These properties make RSF a potential candidate for the fabrication of different types of materials. However, processing even a dilute aqueous solution of RSF leads to a conformational transformation from a random coil/helix-rich (silk I) to a beta-sheetrich (silk II) state. As a consequence, RSF tends to form aggregates and loses its toughness. Working in a direction to address this problem, an aqueous solution of regenerated silk fibroin has been modified with a dual layer of polyethylenimine (PEI) and a PEG-based polymer surfactant (PS). Upon freeze-drying, the RSF-polymer complex forms a solvent-free RSF bioconjugate system and exhibits a soft solid to liquid melting transition at similar to 45 degrees C. The sequential modification with PEI and PS preserves the native-like random coil conformation of RSF up to at least 8 months of storage by not allowing interchain interactions that can lead to aggregation. Rheological and small-angle X-ray scattering measurements show that the solvent-free system is viscoelastic and exhibits a higher order microstructure mediated by the packing of the PS chains, respectively. Temperature-dependent soft solid-liquid-like dual behavior offers applications in injection-based writing, compression molding, and shaping RSF bioconjugates into various types of geometries. Furthermore, the mechanical properties of the RSF bioconjugate system can be modulated by crosslinking with glutaraldehyde vapor at 50 degrees C.
Keywords: RSF liquid; RSF soft solid; silk I conformation; silk liquid; viscoelastic